Hyperinsulinemic hypoglycemia in Beckwith–Wiedemann, Sotos, and Kabuki syndromes: A nationwide survey in Japan. Issue 2 (7th November 2016) - Toda, Naoko; Ihara, Kenji; Kojima‐Ishii, Kanako; Ochiai, Masayuki; Ohkubo, Kazuhiro; Kawamoto, Yutaka; Kohno, Yoshinori; Kumasaka, Sakae; Kawase, Akihiko; Ueno, Yasuhisa; Futatani, Takeshi; Miyazawa, Tokuo; et al.
Abstract : Beckwith–Wiedemann syndrome (BWS) is a congenital overgrowth syndrome that is occasionally associated with hyperinsulinemic hypoglycemia (HH) in the neonatal period. Sotos syndrome (SS) and Kabuki syndrome (KS) are other malformation syndromes that may be complicated with HH, however, the detailed clinical characteristics of HH accompanied with these syndromes remain unclear. We herein conducted a nationwide questionnaire survey in Japan. We sent a primary questionnaire concerning the clinical experience for these syndromes to 347 perinatal care institutions. As a result, 222 departments or hospitals returned the questionnaires and the total numbers of BWS, SS, and KS patients were 113, 88, and 51, respectively. We sent a secondary questionnaire to 31 institutions where patients with these syndromes presented with HH during infancy. The secondary questionnaires were returned from the institutions and the numbers of patients were 16 for BWS, 9 for SS, and 3 for KS, respectively. Then, we compared the clinical characteristics of infants suffering from transient HH with and without these dysmorphic syndromes. As a result, BWS, SS, and KS patients showed significantly larger body size, lower Apgar scores, higher insulin levels at HH, and shorter durations of HH than non‐dysmorphic infants with transient HH. We propose that a careful observation for the signs of HH, even if not specific to the syndromes, is important for the diagnosis of patients with BWS, SS, and KS in the postnatal period. © 2016 Wiley Periodicals, Inc.